Privatization and the Market for Corporate Control - J. Harold Mulherin; Jeffry M. Netter; Michael Stegemoller (Claremont McKenna College, Department of Economics, 2001)
We study the wealth effects of the mergers of privatized firms. Our sample entails 39 privatized firms that subsequently become targets of a takeover and 52 privatized firms that become bidders in mergers. Our results indicate that target firms experience a 12 percent increase in equity value at the announcement of a merger. The bidding firms experience a positive but insignificant change in equity value at merger announcement. The results indicate that mergers result in net wealth creation for privatized firms and are consistent with property rights/agency cost theory. The results also offer global, non-U.S. evidence that mergers create wealth.
Keywords: 330